Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1046/j.1462-2920.1999.00045.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel bacterial endosymbionts of Acanthamoeba spp. related to the Paramecium caudatum symbiont Caedibacter caryophilus

Abstract: Acanthamoebae are increasingly being recognized as hosts for obligate bacterial endosymbionts, most of which are presently uncharacterized. In this study, the phylogeny of three Gram-negative, rod-shaped endosymbionts and their Acanthamoeba host cells was analysed by the rRNA approach. Comparative analyses of 16S rDNA sequences retrieved from amoebic cell lysates revealed that the endosymbionts of Acanthamoeba polyphaga HN-3, Acanthamoeba sp. UWC9 and Acanthamoeba sp. UWE39 are related to the Paramecium caudat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
135
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(141 citation statements)
references
References 39 publications
5
135
0
1
Order By: Relevance
“…The analysis of the 18S rDNA proved to be an effective tool for describing dissimilarities in the genus, thus identifying 12 distinct sequence types (T1-T12) [3,9]. Three more sequence types, T13 [4], T14 [5] and T15 [6], so far not related to a precise pathogenic picture, have been further described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of the 18S rDNA proved to be an effective tool for describing dissimilarities in the genus, thus identifying 12 distinct sequence types (T1-T12) [3,9]. Three more sequence types, T13 [4], T14 [5] and T15 [6], so far not related to a precise pathogenic picture, have been further described.…”
Section: Discussionmentioning
confidence: 99%
“…The taxonomy of the genus is mainly based on morphological features such as size and cyst morphology [2], and only recently the application of molecular tools, in particular sequencing of 18S rRNA genes, has allowed the classification of Acanthamoeba into 15 genotype groups designated as T1-T15 [3][4][5][6][7]. Amoebic keratitis is caused by a wide variety of Acanthamoeba spp., most of which belonging to the T4 rDNA complex [3].…”
Section: Introductionmentioning
confidence: 99%
“…By analysing more than 50 strains from the three morphogroups, they identified 12 sequence types or genotypes, named T1 to T12, where each genotype should correspond to natural species or species complex (Gast et al 1996;Stothard et al 1998). This approach has been largely adopted, and three new genotypes have been established, called T13 to T15 (Horn et al 1999;Gast 2001;Hewett et al 2003). …”
Section: Introductionmentioning
confidence: 99%
“…Sequencing the complete 18S rDNA, ranging between 2,300-2,700 base pairs (bp), provided sufficient data for reliable determination of the relationships among particular genera and toward understanding their phylogenesis (Gast et al 1996;Stothard et al 1998). Research carried out to date has revealed that the new Acanthamoeba classification system based on 18S rDNA consists of 15 different sequence types: T1-T12 (Stothard et al 1998), T13 (Horn et al 1999), T14 (Gast 2001), and T15 (Hewett et al 2003).…”
mentioning
confidence: 99%